Apresiasi Masyarakat Terhadap Tari Gubang di Desa Candi Palmatak Kabupaten Kepulauan Anambas Provinsi Kepulauan Riau - Tamara Yuniar; Yahyar Erawati (Advances In Education Journal, 2025)
Tari Gubang is a traditional performing art of the Malay community in Candi Village, Anambas Islands Regency, Riau Islands Province, performed during weddings and other customary ceremonies. This study aims to describe the forms of community appreciation for Tari Gubang based on Bastomi’s four stages of art appreciation: observing, internalizing, evaluating, and appreciating. This qualitative descriptive research employed non-participant observation, structured interviews, and documentation as data collection techniques. Ten purposively selected participants were involved, including community leaders, dancers, artists, and audience members. The results show that the community displays a relatively high appreciation, particularly in observing and evaluating the elements of dance such as movements, costumes, music, and masks. Emotional involvement is evident through applause and participation. However, limited understanding of symbolic and aesthetic values remains. Despite changes in presentation media, such as the use of electronic organ music, strong community participation remains key to preserving Tari Gubang in the face of modernization.